Folk Music: : Property of the Peasantry? - C. Rouse, Andrew (FOCUS: Papers in English Literary and Cultural Studies, 1998)
There is a prevalence among people to look upon folk music as something quaint, pastoral and ancient, as though God when creating the world had equipped each nation with three hundred or so folk songs and commanded its people to care for them as best they could. Folk music is looked upon by one part of the community as inviolable and sacred, by another as irrelevant and out-of-date. Neither attitude does any good to the musical oral tradition.